Absolute and relative kinetic changes of high-sensitivity cardiac troponin T in acute coronary syndrome and in patients with increased troponin in the absence of acute coronary syndrome - Müller-Hennessen, Matthias; Biener, Moritz; Vafaie, Mehrshad; Dörr, Susanne Katharina; Keller, Till; Blankenberg, Stefan; Katus, Hugo; Giannitsis, Evangelos (Clinical chemistry, 2012)
BACKGROUND: We evaluated kinetic changes of high-sensitivity cardiac troponin T (hs-cTnT) in patients with acute coronary syndrome (ACS) and patients with hs-cTnT increases not due to ACS to rule in or rule out non-ST-segment elevation myocardial infarction (STEMI). METHODS: hs-cTnT was measured serially in consecutive patients presenting to the emergency department. Patients with ACS who had at least 2 hs-cTnT measurements within 6 h and non-ACS patients with hs-cTnT concentrations above the 99th percentile value (14 ng/L) were enrolled to compare absolute and relative kinetic changes of hs-cTnT. RESULTS: For discrimination of non-STEMI (n = 165) in the entire study population (n = 784), the absolute δ change with the ROC-optimized value of 9.2 ng/L yielded an area under the curve of 0.898 and was superior to all relative δ changes (P < 0.0001). The positive predictive value for the absolute δ change was 48.7%, whereas the negative predictive value was 96.5%. In a specific ACS population with exclusion of STEMI (n = 342), the absolute δ change with the ROC-optimized value of 6.9 ng/L yielded a positive predictive value of 82.8% and a negative predictive value of 93.0%. In comparison to the ≥20% relative δ change, the ROC-optimized absolute δ change demonstrated a significantly added value for the entire study population and for the ACS cohort (net reclassification index 0.331 and 0.499, P < 0.0001). CONCLUSIONS: Absolute δ changes appear superior to relative δ changes in discriminating non-STEMI. A rise or fall of at least 9.2 ng/L in the entire study population and 6.9 ng/L in selected ACS patients seems adequate to rule-out non-STEMI. However, δ-values are useful to rule-in non-STEMI only in a specific ACS population.